Synthesis, characterization and activity pattern of carbon nanofibers based copper/zirconia catalysts for carbon dioxide hydrogenation to methanol: Influence of calcination temperature - Ud Din, I. (Elsevier, 2015)
A series of novel carbon nanofibers (CNFs) supported bimetallic copper/zirconia catalysts are synthesized by deposition precipitation method and calcined at different temperatures. Calcined catalysts are characterized by various techniques like X-ray diffraction, N2 adsorption-desorption, N2O chemisorption, high resolution transmission electron microscopy, temperature programmed reduction, X-ray photoelectron spectroscopy and temperature programmed desorption (CO2 & NH3). The structure-activity correlation is discussed in details. The results demonstrate 450 Â°C as optimum calcination temperature for methanol synthesis rate with CO2/H2 feed volume ratio of 1:3. CO2 conversion is found to be directly proportional to copper metallic surface area (SCu), while a linear relationship is observed between methanol synthesis rate and fraction of dispersed Cu. Â© 2014 Elsevier B.V. All rights reserved.